Virtual Socialization, Sharing and Loneliness Level of Primary School Teachers: A Case Study of Famagusta, North Cyprus - Valiyeva, Lamiya (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
In social sciences environment is becoming very essential in any given field. Virtual learning environment is one of the on-going trends in our primary education today. In fact, it has been increasingly luring the social scientists who dedicate most of their studies in field researches. The main purpose of this study is to find out teachers perspective about a virtual learning environment, with regards to virtual socialization, virtual sharing and to investigate the loneliness level of primary school teachers in virtual environment. This thesis make use of a mixed approach in data collection, as data will be retrieved from the participant with the use of a questionnaire aiming to evaluate teachers’ loneliness level in virtual learning environments that will be administered among 153 instructors in 32 Primary schools within the Famagusta District of North Cyprus. In the same vein, a semi-structured interview will be carried out. This study indicates that there is a firm correlation between teachers’ attitudes and virtual learning environments. The main findings of this study show that the level of teachers’ virtual socialization is higher than their loneliness level, and the teachers’ level of virtual sharing was at a lowest level. Keywords: Environment, Virtual Learning, Virtual Learning Environment, Famagusta, North Cyprus

ÖZ: Sosyal ortamlarda yapılan saha çalışmaları, birçok sosyal disiplin açısından özel bir öneme sahiptir. Günümüzde özellikle temel eğitim alanında artan bir ivme sergileyen ve öğrenme süreçlerinin önemli bir parçasına dönüşen sanal öğrenme ortamları, saha çalışmasına önem veren araştırmacıların büyük ilgisini çekmektedir. Bu çalışmanın temel amacı öğretmenlerin sanal öğrenme ortamlarına yönelik düşüncelerini, öğrencilerinin sanal ortamlarda sosyalleşmelerine ve sanal paylaşımlarda bulunmalarına nasıl baktıklarını araştırmak, ayrıca ilkokul öğretmenlerinin sanal ortamlardaki yalnızlık düzeylerini ortaya koymaktır. Bu tez araştırması, Kuzey Kıbrıs’ın Gazimağusa şehrinde bulunan 32 ilkokulda eğitim veren toplam 153 öğretmeni kapsamaktadır. Araştırmada, veri toplama aşamasında karma bir yaklaşım benimsenerek başlıca iki temel araçtan yararlanılmıştır. Araştırma içerisinde ilgili katılımcılarla, öğretmenlerin sanal öğrenme ortamındaki yalnızlığını ölçmeye yönelik bir anket yürütülmüş, aynı zamanda ikinci bir veri toplama aracı olarak yarı yapılandırılmış görüşme tekniğine başvurulmuştur. Bu çalışma, öğretmenlerin tutumlarıyla sanal öğrenme ortamları arasında sıkı bir ilişki olduğunu ortaya koymaktadır. Araştırma sonucunda elde edilen temel bulgular, katılımcı öğretmenlerin sanal sosyalleşme düzeylerinin yalnızlık düzeylerinden daha yüksek olduğunu ve sanal paylaşımın en düşük düzeyde gerçekleştiğini göstermektedir. Anahtar kelimeler: Sosyal Ortam, Sanal Öğrenme, Sanal Öğrenme Ortamı, Gazimağusa, Kuzey Kıbrıs
Master of Science in Information and Communication Technologies in Education. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Education, Dept. of Information and Communication Technologies in Education, 2016. Supervisor: Assoc. Prof. Dr. Ersun İşçioğlu.
Keywords: Information and Communication Technologies in Education-Virtual Learning; Instructor Attitudes-Information Communication Technologies-Virtual Learning Environments; Education - Computer network resources; Educational Technology-E-Learning; Environment; Virtual Learning; Virtual Learning Environment; Famagusta; North Cyprus; Information and Communication Technologies in Education